-2(10-3b)=6(b+3)+2

Simple and best practice solution for -2(10-3b)=6(b+3)+2 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -2(10-3b)=6(b+3)+2 equation:



-2(10-3b)=6(b+3)+2
We move all terms to the left:
-2(10-3b)-(6(b+3)+2)=0
We add all the numbers together, and all the variables
-2(-3b+10)-(6(b+3)+2)=0
We multiply parentheses
6b-(6(b+3)+2)-20=0
We calculate terms in parentheses: -(6(b+3)+2), so:
6(b+3)+2
We multiply parentheses
6b+18+2
We add all the numbers together, and all the variables
6b+20
Back to the equation:
-(6b+20)
We get rid of parentheses
6b-6b-20-20=0
We add all the numbers together, and all the variables
-40!=0
There is no solution for this equation

See similar equations:

| 5·(x-7)-4x=11 | | 6(5-8w)=-66 | | 8x+3=8x | | 12x^2=19x+10 | | (8x–30)+(4x)=90 | | -4(-10-6n)=2(9n-7) | | 5d=3(d+6) | | 6n+3=16 | | 4(q-13)-12=-4 | | x2−9x−15=−5 | | (x*3)+5=20 | | x+2÷8=2 | | 167=60-x | | 2x-7=6(x+3) | | x-6-3x=-8-8x+5 | | 9y=10y-19 | | 11+5k=2+3k-3 | | 20-8u-8u=4(-5u-11) | | 12x^2=19x*10 | | 5•(x-7)-4=11 | | 4/9(x)=-8 | | 24+m+85=685 | | -18=10a+2 | | -16+11q=-14q+9(-19q+20) | | 4/9(x)=8 | | 7x=0.5(2x+4) | | 8x-45-10=15+6x | | 4b+12=84 | | B+9b+2=12 | | —16+z=20 | | /1x+11=15 | | 41/2x+7=12 |

Equations solver categories